2014
DOI: 10.1111/jgs.13181
|View full text |Cite
|
Sign up to set email alerts
|

Significant Unmet Oral Health Needs of Homebound Elderly Adults

Abstract: Objectives Older adults with serious illness are increasingly becoming homebound. By nature of their homebound status they lack access to basic services including dental care. We conducted a study to assess the oral health status, dental utilization and dental needs of the homebound elderly and to determine whether medical diagnoses or demographic factors influenced perceived oral health. Design Cross-sectional analysis Methods A total of 125 homebound patients received a comprehensive clinical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 28 publications
3
65
2
4
Order By: Relevance
“…Th e most common oral diseases among the elderly are dental caries, tooth loss, gingivitis, periodontitis, decreased salivary fl ow, candidiasis, and oral cancer 2,6 . Th ese are even more significant among institutionalized elderly people 7,8 . Prevention of oral diseases is greatly infl uenced by salivary fl ow; furthermore, saliva protects the oral mucosa and the teeth, plays a role in taste perception, food-bolus formation, swallowing, communication and digestion 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Th e most common oral diseases among the elderly are dental caries, tooth loss, gingivitis, periodontitis, decreased salivary fl ow, candidiasis, and oral cancer 2,6 . Th ese are even more significant among institutionalized elderly people 7,8 . Prevention of oral diseases is greatly infl uenced by salivary fl ow; furthermore, saliva protects the oral mucosa and the teeth, plays a role in taste perception, food-bolus formation, swallowing, communication and digestion 9 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a progressive increase in the proportion of the senior residents with severe disabilities, ranging from 25.5% for the population between 65 and 74, to 72.5% for years 85 and over. There were wide variations in the proportion of civilian residents 65 years and over with serious disabilities living in different areas of the country, ranging from 31% in Connecticut, Delaware, Wisconsin and Maryland to 49% in Puerto Rico …”
Section: Demographicsmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention reported that in 2014, among the 65 years and older population, 56.1% of individuals with a disability, compared to 71.7% of individuals with no disabilities, reported a dental visit in the past year. In addition, a smaller per cent of Hispanic and black seniors reported a dental visit the past year …”
Section: Demographicsmentioning
confidence: 99%
“…A previous study showed domiciliary dental care improved the availability of dental care services for older adults with a poor general health condition . However, studies in several countries reported that the proportions of those receiving domiciliary dental care were low and there might be unmet need, especially among homebound older adults . Little is known about factors associated with the use of domiciliary dental care among homebound older adults.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Previous studies have shown that limited availability of dental care services contributed to deteriorated oral conditions among older adults. 1,2,4 Preserving oral health in this population is essential, because oral health is related to general health, including dementia, aspiration pneumonia, diabetes mellitus, nutrition status and quality of life. [5][6][7] A previous study showed domiciliary dental care improved the availability of dental care services for older adults with a poor general health condition.…”
Section: Introductionmentioning
confidence: 99%